2016
DOI: 10.1039/c6sc01567k
|View full text |Cite
|
Sign up to set email alerts
|

Metallacarboranes as tunable redox potential electrochemical indicators for screening of gene mutation

Abstract: The electrochemical behaviour of metallocarborane sodium salts and their interactions with DNA have been studied. They are shown to be selective redox indicators with wide-ranging potential as electrochemical indicators in DNA biosensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
6
37
1
Order By: Relevance
“…Cells showedv ery intensec ytoplasmic fluorescence, with some patterns resembling the microtubule cytoskeleton distribution (red arrows). [58] Considering these results, and extrapolating them to our findings, it is likely that the strongi nteraction of COSAN with proteins in the cytoplasm prevents the compounds from diffusing into the nuclei. These data suggest that 7 could be simultaneously exertings ome kind of chemical fixation while staining the cells.…”
Section: Bioimagingsupporting
confidence: 61%
See 1 more Smart Citation
“…Cells showedv ery intensec ytoplasmic fluorescence, with some patterns resembling the microtubule cytoskeleton distribution (red arrows). [58] Considering these results, and extrapolating them to our findings, it is likely that the strongi nteraction of COSAN with proteins in the cytoplasm prevents the compounds from diffusing into the nuclei. These data suggest that 7 could be simultaneously exertings ome kind of chemical fixation while staining the cells.…”
Section: Bioimagingsupporting
confidence: 61%
“…[53] These are significant features fort he design of pharmaceuticals, making this anion and its derivatives highly promising candidates for biomedical applications. [58,59] In view of the broad studies based on the potential applicationoft hese boron clusters in biomedicine, [60,61] here they have been linked to organotin complexes to evaluate their capacity to serve as nucleoli markers for cell imaging in vitro. [58,59] In view of the broad studies based on the potential applicationoft hese boron clusters in biomedicine, [60,61] here they have been linked to organotin complexes to evaluate their capacity to serve as nucleoli markers for cell imaging in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular uptake and distribution studies of Na[COSAN] in cancer cells has shown that [COSAN] − is retained in the nuclear fractions, which contain most of the cell genetic material organized as multiple long linear DNA molecules in complex structures. To date, only the studies related to DNA interaction with Na[FESAN] are reported . Here, we have exploited the interaction between Na[COSAN] and DNA molecules to form a new nanohybrid biomaterial.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only the studies related to DNA interaction with Na[FESAN] are reported. [19] Here, we have exploited the interaction between Na[COSAN] andD NA molecules to form a new nanohybrid biomaterial.S pecifically,s pectrophotometric measurements (IR and Raman) have been used to prove the interaction, and meltingt emperature (Tm), UV,c yclic voltammetry,a nd CD techniques wereu sed to discern on the nature of such interaction. Later,once proventhe formationo ft he nanohybridb iomaterial,t he hydrodynamic diameter (Ø HYD )o ft he dispersed Na[COSAN] (0.1 mm) after the addition of different concentrations of CT-dsDNA, in aqueouss olution, at room temperaturef or samples in PB (0.1 m, pH 7.0) were studied.F inally, the nanohybrid biomaterial wasv isualized by optical, TEM, and CryoTEM microscopies.…”
Section: Cellular Viabilitymentioning
confidence: 99%
See 1 more Smart Citation